Stalin's gamble : the search for allies against Hitler, 1930-1936 - Carley, Michael Jabara, 1945- (University of Toronto Press, 2023)
"Shedding light on the origins of the Second World War in Europe, Stalin's Gamble aims to create a historical narrative of the relations of the USSR with Britain, France, the United States, Poland, Germany, Italy, Czechoslovakia, and Romania during the 1930s. The book explores the Soviet Union's efforts to organize a defensive alliance against Nazi Germany, in effect rebuilding the anti-German Entente of the First World War. Drawing on extensive research in Soviet as well as Western archives, Michael Jabara Carley offers an in-depth account of the diplomatic manoeuvrings which surrounded the rise of Hitler and Soviet efforts to construct an alliance against future German aggression. Paying close attention to the beliefs and interactions of senior politicians and diplomats, the book seeks to replace one-sided Western histories with records from both sides. The book also offers an inside look at Soviet foreign policy making, with a focus on Stalin as foreign policy maker and his interactions with his colleagues. Told in a fascinating narrative style, Stalin's Gamble attempts to see the European crisis of the 1930s through Soviet eyes."--